Susceptibility of the Asian citrus psyllid Diaphorina citri to entomopathogenic nematodes - Doneze, Gabriela Souza; Alves, Viviane Sandra; Leite Junior, Rui Pereira (Semina: Ciências Agrárias, 2024)
The Asian citrus psyllid, Diaphorina citri Kuwayama, 1908, (Hemiptera: Psylloidea: Liviidae), is one of the most important pests for citrus production, as it is the main vector of 'Candidatus Liberibacter spp.' bacteria, the causal agents of Huanglongbing (HLB). Applications of chemical insecticides are currently the primary method for psyllid control, but have shown low efficiency and problems such as the development of resistant insect populations, and increased risks for the human health and the environment. Thus, the aim of this study was to assess the use of entomopathogenic nematodes (EPNs) as an alternative and sustainable strategy for the control of D. citri. Initially, the activity of 10 EPN isolates of the genera Heterorhabditis and Steinernema was tested against D. citri. Assessments were carried out on D. citri adults under laboratory conditions. Next, the efficiency of the concentrations of 50, 100, 150, and 200 Infective Juveniles (IJs)/cmÂ² of the UENP 06 and NEPET 11 EPN isolates in causing the death of D. citri adults was tested. The NEPET 11 and UENP 06 isolates, both Heterorhabditis amazonensis, were the most effective in controlling psyllids, achieving confirmed mortality rates of 68.25 and 53.00%, respectively. In all IJ concentrations tested, these isolates caused confirmed mortality of D. citri adults, with no significant differences between concentrations and EPN isolates.